Sundanese culture-based character learning program "Gelar Nyunda" (Case study at SDN 172 Andir Kidul, Bandung City) - Wida Widaningsih; Y. T. Herlambang (Curricula: Journal of Curriculum Development, 2025)
The issue of low psychological well-being in elementary schools, mainly due to physical, verbal, and social bullying, is a concern in the 2023 Education Report Card report. This research aims to create a more positive school climate by strengthening character based on Sundanese local culture. Values such as silih asih, silih asah, and silih asuh are integrated into the “Gelar Nyunda” co-curricular program, which is designed using a deep learning approach. The program combines traditional games (Kaulinan Barudak) and colossal angklung performances as a medium for character internalization in a fun and contextual way. The research employed a qualitative approach with a case study design over one year (July 2023-August 2024). Data collection techniques included observation, interviews, and documentation. Participants consisted of students in grades III and VI, principals, teachers, and homeroom teachers. The results showed that the “Gelar Nyunda” program received a positive response; students seemed enthusiastic, physically and emotionally active, and exhibited a change in attitude, becoming more polite and empathetic. The findings suggest that a culture-based approach, rooted in local context, is effective in shaping character and enhancing the climate of wellbeing in elementary schools.    Abstrak Permasalahan rendahnya kesejahteraan psikologis di sekolah dasar, terutama akibat perundungan fisik, verbal, dan sosial, menjadi perhatian dalam laporan Rapor Pendidikan tahun 2023. Penelitian ini bertujuan menciptakan iklim sekolah yang lebih positif melalui penguatan karakter berbasis budaya lokal Sunda. Nilai-nilai seperti silih asih, silih asah, dan silih asuh diintegrasikan dalam program ko-kurikuler “Gelar Nyunda” yang dirancang menggunakan pendekatan deep learning. Program ini menggabungkan permainan tradisional (Kaulinan Barudak) dan pertunjukan angklung kolosal sebagai media internalisasi karakter secara menyenangkan dan kontekstual. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus selama satu tahun (Juli 2023–Agustus 2024). Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi. Partisipan terdiri dari murid kelas III dan VI, kepala sekolah, guru, dan wali kelas. Hasil menunjukkan bahwa program “Gelar Nyunda” mendapat respons positif; murid tampak antusias, aktif secara fisik dan emosional, serta menunjukkan perubahan sikap menjadi lebih santun dan empatik. Temuan ini mengindikasikan bahwa pendekatan berbasis budaya lokal efektif dalam membentuk karakter dan meningkatkan iklim well being di sekolah dasar. Kata Kunci: budaya Sunda; kearifan lokal; pembelajaran ko-kurikuler; penguatan karakter